Pyrexia of unknown origin in a 1-year-old child: How far should we go? A case report - Henrietta U Okafor; Ngozi S Ibeziako; Josephat M Chinawa; Tobechukwu Chinenye Ezike (International Journal of Medicine and Health Development, 2021)
Introduction: Pyrexia of unknown origin (PUO) still remains a challenge in paediatric practice. Appropriate history, physical examination, and exhaustive investigations are crucial in managing cases of PUO. Case Presentation: UU, was a 1-year-old female, who was seen at our facility on 16 January 2020, with a 4-day history of fever. Fever was high grade and intermittent. Examination revealed pyrexia of 38°c and no other remarkable findings. Lassa fever virus serology, hepatitis B surface antigen, hepatitis C surface antigen, C-reactive protein, erythrocyte sedimentation rate, full blood count, blood culture (with Bactec), malarial parasite, Mantoux, and CXR were all requested. Results of all these investigations were negative. Echocardiography done showed a 0.23 cm² vegetation at the septal leaflet of the tricuspid valve. A diagnosis of infective endocarditis was made and intravenous vancomycin, ceftriaxone, and metronidazole were commenced. Weekly urinalysis and serum electrolyte urea and creatinine monitoring were documented. After a 3-week course of intravenous antibiotics, patient still had fever with temperature higher than 38°c. A diagnosis of PUO was made and a follow-up plan was to do a bone marrow aspiration to rule out leukaemia and serology to rule out connective tissue disease. Conclusion: In managing a child with PUO, detailed history, appropriate physical examination and exhaustive investigations should be done. This is crucial in that even if diagnosis is not reached, several causes of PUO could have been ruled out.